The figure of Aristotle in the domestic intellectual atmosphere of the 19th century - Pavlova, Daria Aleksandrovna (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика, 2022)
A researcher dealing with the topic of the presence of Aristotle’s philosophy in the modern Russian space of the humanities is faced with the task of comprehending the origins of the attitude towards Aristotle in the history of Russian science. Aristotle in Russia, unlike Europe, is represented in a rather limited way, and even where he is present, modern Russian philosophy uses a rather narrow layer of thought from his heritage. The article is devoted to the theme of a special attitude to the fi gure of Aristotle in the fi eld of domestic social and humanitarian thought of the XIX century. During the formation of Russian philosophy as an independent phenomenon of global culture, Aristotle also falls into the fi eld of view of its founders. The interest in Aristotle was not originally of a scientifi c (historical-philosophical or philological) nature, but stemmed from current socio-political disputes, which would later become known as the disputes between Slavophiles and Westernizers. Aristotle in this case acts as a part of world culture, in which domestic intellectuals of the 19th century claim to a special place. This era is considered as a period that laid the basic principles of attitude towards Aristotle in Russia in the 20th century. Such principles are the attitude towards Aristotle as a historian of science and as a part of world culture.